(untitled) (International Seven Journal of Health Research, 2024)
Case presentation: A 59-year-old asymptomatic male patient was admitted for treatment of diffuse B-cell non-Hodgkin’s lymphoma. Contrast-enhanced CT scans revealed a nodular lesion with intense enhancement, measuring 4.5 cm in the left paravertebral region, with fine calcification in between, located in the D9 and D10 planes, where he was referred to the thoracic surgery team.